IMPLEMENTASI METODE SOSIODRAMA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM MATERI BEREMPATI ITU MUDAH MENGHORMATI ITU INDAH DENGAN PENDEKATAN SAVI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII D DI SMPN 2 TUGU TRENGGALEK TAHUN PELAJARAN 2016-2017 - Imam Mashudi; Nurul Iman; Sigit Dwi Laksana (Universitas Muhammadiyah Ponorogo, 2017)
The researcher have taken the location of this research in SMPN 2 Tugu Trenggalek by the reason it is one of SMPN in Tugu subdistrict that the progress is quick, with the result that many students want to study in SMPN 2 Tugu Trenggalek. The progress indicators can be looked from many events have reached by students of SMPN 2 Tugu Trenggalek. Except that SMPN 2 Tugu Trenggalek is one of SMPN in Tugu subdistrict to be pilot project of K13.The purposes of this research to describe the implementation of sociodrama method on PAI lesson in berempati itu mudah menghormati itu indah material by using SAVI approach and analise the increasing of the result study of students from the implementation sociodrama method by using SAVI approach in berempati itu mudah menghormati itu indah material. This research is the Classroom Action Research (PTK), where consists two cycle and in the ane cycle consists two meeting. Technic of collecting data have taken from the result of interview, observation, documentation and result of field note. Correction of data validation have used triangulation method based on source. Analise data in this research have used description analistic by collecting data, processing, analise and reduce to be conclution. The result of the research have appointed to increasing study result from precycle the classical completeness is 46,43% by everage 52,86 increase on cycle I the classical completeness 67,86 % by everage 66,71 and on cycle II the classical completeness to be 82,14% by everage 78,36.